2017
DOI: 10.1126/science.aao7294
|View full text |Cite
|
Sign up to set email alerts
|

Variation in theAvrSr35gene determinesSr35resistance against wheat stem rust race Ug99

Abstract: f. sp. () causes wheat stem rust, a devastating fungal disease. The resistance gene confers immunity against this pathogen's most virulent races, including Ug99. We used comparative whole-genome sequencing of chemically mutagenized and natural isolates to identify a fungal gene named that is required for avirulence. The gene encodes a secreted protein capable of interacting with Sr35 and triggering the immune response. We show that the origin of isolates virulent on is associated with the nonfunctionalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
170
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(200 citation statements)
references
References 28 publications
4
170
2
Order By: Relevance
“…Changes in pathogen effectors, including amino acid changes in the contact surface, loss-of-function mutations, or deletions, can help the pathogen avoid detection by the corresponding NBS-LRR genes Salcedo et al, 2017). As a result, many all-stage resistance genes are defeated within a few years of their commercial deployment by the rapidly evolving rust populations.…”
mentioning
confidence: 99%
“…Changes in pathogen effectors, including amino acid changes in the contact surface, loss-of-function mutations, or deletions, can help the pathogen avoid detection by the corresponding NBS-LRR genes Salcedo et al, 2017). As a result, many all-stage resistance genes are defeated within a few years of their commercial deployment by the rapidly evolving rust populations.…”
mentioning
confidence: 99%
“…In P. infestans , polymorphic amino acids K 80 and I 103 of AVR3a contribute to detection by R3a with K 80 having a critical effect (Bos et al ., ), and amino acid 69 of AVRblb2 is critical for detection by Rpi‐blb2 (Oh et al ., ). More recently, variations in the AvrSr35 gene determined Sr35 resistance against wheat stem rust race Ug99 (Salcedo et al ., ). These studies, together with our findings, uncovered the diversity of mechanisms that have evolved in the effectors of plant pathogens to avoid detection.…”
Section: Discussionmentioning
confidence: 97%
“…Two recent studies demonstrated the degree to which genomics has impacted the field by combining genomics and resequencing approaches to identify AvrSr35 and AvrSr50 , two P. graminis f. sp. tritici avirulence effector genes (see details in Section ; Chen et al ., ; Salcedo et al ., ). It is very likely that population genomics and genome‐wide association studies will unveil even more key pathogenicity determinants over the next few years.…”
Section: Rusts In the Genomics Era: The Ever‐expanding List Of Candidmentioning
confidence: 97%